2019
DOI: 10.4103/nmj.nmj_57_19
|View full text |Cite
|
Sign up to set email alerts
|

Occupational hazards and health problems among butchers in Uyo, Nigeria

Abstract: Introduction:Butchers are exposed to various types of hazards in the course of their work, which could lead to health problems of varying severity. The aim of this study was to identify the occupational hazards and health problems of butchers in Uyo and also assess the physical conditions of their slaughter facilities.Materials and Methods:A descriptive cross-sectional study was carried out among 157 butchers in Uyo using a semi-structured questionnaire for data collection. Facility assessment was made using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 13 publications
0
14
1
Order By: Relevance
“…None of the butchers was observed to use any personal protective equipment like googles, gloves, foot wears, aprons or mask. Similar studies in India and Nigeria in 2019 however, reported the use of some personal protective devices by a few of their participants [24,27]. Use of PPDs prevent meat contamination and also protect butchers from meat borne diseases [24].…”
Section: Key Informant Interview With Heads Of the Abattoirsmentioning
confidence: 84%
See 2 more Smart Citations
“…None of the butchers was observed to use any personal protective equipment like googles, gloves, foot wears, aprons or mask. Similar studies in India and Nigeria in 2019 however, reported the use of some personal protective devices by a few of their participants [24,27]. Use of PPDs prevent meat contamination and also protect butchers from meat borne diseases [24].…”
Section: Key Informant Interview With Heads Of the Abattoirsmentioning
confidence: 84%
“…Butchers who refused to give consent and those not present on duty on the dates of visitations were excluded from the study. A minimum sample size of 39 was determined using the formula for estimating single proportion for cross-sectional studies with a prevalence of 0.026 being the prevalence of use of tyre in defurring cows in a previous study [27], z of 1.96 and sampling error of 0.05. The sample size was, however, increased to 42 after adding 10% attrition rate.…”
Section: Uyo Capital City Territory Consists Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Nigeria are mostly handled by people who are unaware of the slaughterhouse and environmental safety policies (Johnson & Etokidem, 2019), especially regarding possible microbial contaminations during meat processing (Egesi et al, 2019). Wastewater from…”
Section: Activities Of Meat Processing From Slaughterhouses Inmentioning
confidence: 99%
“…Respiratory symptom among street sweepers were reported in different regions of the world including Tanzania, 3 Iran, 6 India, 7 Nigeria, 47.3% of participants, 8 and in different parts of Ethiopia, such as Dessie and Kombolcha, 45.4%, with the prevalence of cough, 16.54%, phlegm, 15.4%, wheezing, 32.3%, breathlessness, 21.3%, and chest pain, 14.3%, 9 and Addis Ababa, in 2017, 68.9%, 10 and 2018, 70.3%. 11…”
Section: Introductionmentioning
confidence: 99%